Green technology for the production of selenium nanoparticles using cocoa waste - Soroodi, Fatemah; Jamal, Parveen; Ibrahim Ali , Noorbatcha (2015)
Nanoparticles can be synthesised by chemical, physical and biological methods. There are various disadvantages of chemical and physical approaches including release toxic and hazardous and toxic chemicals, high cost of process production beside time consuming. In this study, a novel single step green-synthesis route has been developed for the synthesis of Selenium Nanoparticles using aqueous extract cocoa pod husk (CPH) which is the byproduct generated from cocoa industry. Formation of SeNPs was preliminary confirmed by change in mixture color from light brown to red and UV-vis spectroscopy characterization showed maximum absorption band at 222 nm. Different optimal parameters such as ratio of Na₂SeO₃(aq)/CPHextract(aq), reaction temperature and Na₂SeO₃(aq)/CPH extract (aq) concentration. It is expected that the time of reaction can be reduced by optimization of the process condition